UNIT 16.26 Rapid, Efficient, and Modular Generation of Adenoviral Vectors via Isothermal Assembly. Issue 1 (4th January 2016) - Yang, Yong; Chi, Yudan; Tang, Xinying; Ertl, Hildegund C.J.; Zhou, Dongming
Abstract : Adenoviral vectors have yielded promising results as carriers for gene transfer and vaccines in basic research and clinical applications. However, most common procedures to construct adenoviral vectors and manipulate adenovirus (Ad) genomes are complex and labor‐intensive. An easy and detailed protocol for the rapid, efficient, and modular generation of chimpanzee Ad serotype 68 (AdC68) as a molecular clone via isothermal assembly, which directionally assembles multiple DNA fragments in a single isothermal reaction without restriction enzymes or ligases, is presented. Any serotype of adenovirus with the sequence of genome known can be constructed as a molecular clone by this method. Recombinant adenoviral vectors can be created via one‐step isothermal assembly in <3 days, and recombinant Ads can be rescued within 8 days. This protocol is practical for manipulations of Ad genomes, because an entire Ad genome can be divided into specific fragments within modular plasmids. © 2016 by John Wiley & Sons, Inc.